2015
DOI: 10.5582/irdr.2015.01018
|View full text |Cite
|
Sign up to set email alerts
|

A study of deafness-related genetic mutations as a basis for strategies to prevent hereditary hearing loss in Hebei, China

Abstract: Hearing loss is the most common sensory disorder, and at least 50% of cases are due to a genetic etiology. Two-thirds of individuals with congenital deafness are nonsyndromic. Among the nonsyndromic forms, the large majority are monogenic autosomal recessive traits. The current work summarizes mutations in the GJB2, SLC26A4, 12SrRNA, and GJB3 and their prevalence in 318 students with autosomal recessive nonsyndromic hearing loss at schools for the deaf or special needs schools in 9 cities in Hebei Province, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(38 reference statements)
0
1
1
Order By: Relevance
“…Fifteen patients were found to carry the c.1555A>G homoplasmic mutation in this study, accounting for 1.25% (15/1,201). The frequency of mtDNA 12S rRNA mutations found in the present study was lower than either that reported by Guo et al (2008) in northern Chinese subjects or that reported in the northwest of China (Ma et al, 2016;Zhu et al, 2015). This result may be related to the fact that a majority of our patients had congenital and prelingual deafness.…”
Section: Discussioncontrasting
confidence: 85%
“…Fifteen patients were found to carry the c.1555A>G homoplasmic mutation in this study, accounting for 1.25% (15/1,201). The frequency of mtDNA 12S rRNA mutations found in the present study was lower than either that reported by Guo et al (2008) in northern Chinese subjects or that reported in the northwest of China (Ma et al, 2016;Zhu et al, 2015). This result may be related to the fact that a majority of our patients had congenital and prelingual deafness.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, the SLC26A4 gene is known to be closely associated with delayed-onset hearing loss and is often detected in deaf populations. Zhu et al reported that the rate of homozygous and heterozygous mutations in the SLC26A4 gene was 6.92% (22/318) and 18.55% (59/318), respectively, in 318 students with NSHL in Hebei Province, China (15). Later, the current authors' research group examined patients with a single-allele SLC26A4 mutation revealed by newborn genetic screening for deafness.…”
Section: Introductionmentioning
confidence: 97%